Kualitas Produk, Pelayanan dan Nilai Syariah terhadap Persepsi Mahasiswa Ekonomi Islam untuk Menjadi Nasabah Bank Syariah - Azhar Muttaqin, Dian Azmi Dinaratu (FALAH Jurnal Ekonomi Syariah, 2017)
This study aims to determine how much influence the perception of Islamic economics students about product quality, service quality, and sharia value of interest to become customers of Islamic Bank. The result of data processing shows that the perception of product quality and service quality perception have positive and significant effect on the interest to become the customer of Islamic Bank proven with probability value (sig.) Of 0.000 <0,05. While the variable of perception of syariah value have positive and insignificant effect on interest to become customer of Islamic bank with result of probability value (sig.) Equal to 0,888> 0,05. Variable perception of product quality has the greatest and significant influence to the interest of becoming a customer of Islamic Bank indicated by t value counted 5,042. The perception of product quality, service quality, and sharia value influence 50,7% to interest to become customer of Islamic Bank in view from Adjusted R Square value and 49,3% (100% - 50,7%) influenced by other variable outside variable The selected.